The Analysis of Specialists Supply Changes and their Competence Evaluation Opportunities in Lithuania - Pocius, Arūnas (Lithuanian Journal of Statistics, 2011)
This article aims to analyze the situation and the development of the labor supply in Lithuania. Much attention ispaid to possibilities of competencies identification. The analysis was carried out by using Education indicators of Lithuanianpopulation according to ISCED and classification of Lithuanian Education provided by Statistics Lithuania. Also analysis ofLithuanian labour force (employment survey) data were used. The indicators used in the article include labour supply (labourresources) distribution by education and its separate areas. A key priority of the article is the evaluation of changes in supply. Theanalysis is based on the data of labour force (employment) survey of Statistics Lithuania and its information published aboutspecialists prepared in country educational institutions.